Spatial variability of long-term trends of significant wave heights in the Black Sea - Aydogan, Burak; Ayat, Berna (ELSEVIER SCI LTD, 2018)
This study aims to estimate the spatial variability of the long-term trends of Significant Wave Height (SWH) in the Black Sea. A spectral wave model was used to hindcast 38 years of SWH forced by ECMWF ERA Interim wind fields. Long-term trends were estimated from normalized SWH (NSWH) data, for each month separately, by using two non-parametric methodologies; Line of best fit and the Theil-Sen estimator, and then mapped to show their spatial variability. Maps were generated for both mean SWHs and 95th percentile SWHs, the latter is considered to reflect the trends of the severe sea states. The basin-averaged analysis was also carried out to investigate the general tendency of SWHs in the Black Sea. The significance of the trends was evaluated by using Mann-Kendall test. The annual mean SWH is found to be increasing (up to 1.6%/year) in the eastern part of the Black Sea while the western part has a negative trend (down to -1.2%/year). Long-term analysis of the 95th percentile SWHs revealed steeper trend slopes and higher statistical significance compared to the mean SWH trends, showing that storm SWHs have a higher tendency to increase than the mean SWHs. Statistically significant correlations between climate indices; North Atlantic Oscillation (NAO), Arctic Oscillation (AO), Antarctic Oscillation (AAO), Atlantic Multidecadal Oscillation (AMO), Pacific North American (PNA), East Atlantic (EA), East Atlantic/West Russia (EA/WR), Scandinavia (SCAND), Nino3 and the Black Sea wave fields were identified.
Keywords: Long-term; Trend; Significant wave height; Theil-Sen estimator; Mann-Kendall test; Black Sea; Spatial variability; Climate indices; NORTH-ATLANTIC; WIND-WAVES; ENERGY-RESOURCES; COASTAL REGIONS; REANALYSIS; CLIMATE; MODEL; PACIFIC; IMPACT; Engineering; Oceanography